PENGATURAN PEMILHAN UMUM SEBAGAI SARANA PENINGKATAN PARTISIPASI POLITIK RAKYAT - Gunawan Gunawan (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
The principles of popular sovereignty in this matter are translated in Article 1 paragraph (2) of the 1945 Constitution which expressly regulates sovereignty in the hands of the people and is carried out in accordance with the Constitution. One manifestation of the will of the people) in the framework of implementing popular sovereignty in government administration is to give recognition to citizens to move and be active in determining the form of governmental government. The existence of a constitutional path related to the direct election system of the President and Vice President by the people, has been interpreted by many as a step forward in building democracy. By law, General Election is regulated in Law Number 7 of 2017 concerning General Elections (hereinafter referred to as Law Number 7 of 2017), with consideration that the Election will guarantee the distribution of votes. The phrase